2003
DOI: 10.1111/j.1151-2916.2003.tb03339.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of High‐Density Submicrometer Al2O3 for New Applications

Abstract: Sintered corundum components with submicrometer grain sizes exhibit properties which enable numerous new applications. Wet powder processing is developed to associate minimum grain sizes at highest densities with the lowest population of macrodefects. A closest ratio of powder particle size and sintered grain size is important for obtaining most fine‐grained microstructures. This target was approached best by using powders with particle sizes in the range of 100–200 nm rather than with smaller nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
176
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 19 publications
7
176
0
2
Order By: Relevance
“…However, their RIT values are still far from those found by Krell et al [2] using HIP (72% at 640 nm). Green body shaping was shown to be of crucial importance by Krell et al [21] for natural sintering. Recently, Aman et al [22] have shown that processing the green state also has a strong influence on the optical properties of Spark Plasma Sintered PCA.…”
Section: Introductionmentioning
confidence: 99%
“…However, their RIT values are still far from those found by Krell et al [2] using HIP (72% at 640 nm). Green body shaping was shown to be of crucial importance by Krell et al [21] for natural sintering. Recently, Aman et al [22] have shown that processing the green state also has a strong influence on the optical properties of Spark Plasma Sintered PCA.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, similar relationships between wear rates and grain size are observed in various wear modes, such as erosive wear, abrasive wear, cutting, and grinding 12 . Moreover, the mechanical strength of alumina may be improved when the microstructure shows fine grainsize and residual porosity less than 0.05% 15 . Solid state sintering contributes to grain growth in alumina, because of the high temperatures and holding times applied.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina is a typical engineering ceramic 1,5-7 used in structural applications 7 ; automotive, aerospace, biomedical, and ballistic applications 8 ; and cutting tools 9 . Many studies have shown the influence of microstructure on the mechanical behavior of alumina, and most of them were focused on the effects of grain size [10][11][12][13][14][15][16][17] . A fine-grained microstructure 3,10,11 and narrow range of particle size distribution often result in an improvement of the mechanical behavior of alumina 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…5 From some of these studies, it appeared that achieving "full" density without extensive grain growth can be favored by defect free green body processing. 5,11 Defect free high density green body fabrication gives a more homogeneous porosity distribution. This allows the pores to close as late as possible during the sintering cycle, reduces the sintering temperature 5,11 and retards the occurrence of grain growth.…”
Section: Introductionmentioning
confidence: 99%